Creative union : the professional organization of Soviet composers, 1939-1953 - Tomoff, Kiril (Cornell University Press, 2006)
Central to Tomoff's argument is the institutional authority and prestige that the musical profession accrued and deployed within Soviet society, enabling musicians to withstand the postwar disciplinary campaigns that were so crippling in other artistic and literary spheres."--Jacket.
Keywords: Soi͡uz kompozitorov SSSR -- History.; Soiuz kompozitorov SSSR.; Soi͡uz kompozitorov SSSR; Sojuz Kompozitorov SSSR; Goria, A.; Sovetskaja Associacija Meždunarodnogo Prava; Music and state -- Soviet Union.; Musicians -- Labor unions -- Soviet Union.; Music -- Soviet Union -- History and criticism.; Musique -- Politique gouvernementale -- URSS.; Musiciens -- Syndicats -- URSS.; Musique -- URSS -- Histoire et critique.; MUSIC -- Genres & Styles -- Classical.; MUSIC -- Reference.; Music; Music and state; Musicians -- Labor unions; Soviet Union; Berufsverband; Sowjetunion; Komponist; Componisten.; Vakverenigingen.; Sovjet-Unie.; Criticism, interpretation, etc.; History